Treating TRAPS Syndrome with a Previously Undescribed TNF α Gene Receptor Mutation Successfully with Canakinumab - T. V. Sleptsova; E. I. Alexeeva; K. V. Savostyanov; A. A. Pushkov; T. M. Bzarova; K. B. Isaeva; R. V. Denisova (Union of pediatricians of Russia, 2016)
The article presents an observation of one of the most common autoinflammatory syndromes - TRAPS (periodic syndrome associated with a mutation in the TNF α receptor gene). During a molecular-genetic examination of a 9-year-old child, a c.337_339del deletion in the heterozygous state of the TNFRSF1A gene exon 04, leading to a p.Glu113del amino acid deletion, was found. This mutation has not been described previously in TRAPS patients, and according to computer analysis (Alamut Visual) the issue is pathogenic. This observation indicates the presence of families with TRAPS in the Russian population, who can have «atypical» TNFRSF1A gene mutations. A successful use of monoclonal antibodies to interleukin 1 - canakinumab - in the patient is described. As a result, fever and abdominal syndromes have completely stopped, while knee joints pain decreased a day later. After a week of treatment, the child's disease activity laboratory indices returned to normal (ESR, C-reactive protein). No exacerbations were fixed over the next 32 weeks. No adverse effects were registered during canakinumab therapy. Thus, canakinumab has demonstrated a high level of effectiveness and safety for the patient suffering from a periodic syndrome associated with a mutation in the TNF α  gene receptor. This indicates therapeutic use prospects for the interleukin 1 β blocker in TRAPS syndrome patients.